Intracorporeal versus extracorporeal anastomosis in laparoscopic right colectomy: short-term outcomes - Gil, Inês Campos (2018)
Background: Recently, there has been a growing enthusiasm in developing new techniques of intracorporeal anastomosis following laparoscopic colectomy, which are more challenging than extracorporeal techniques. However, the evidence is still lacking regarding the outcomes’ comparison of both procedures. Methods: We designed a retrospective study comparing intracorporeal and extracorporeal anastomosis following laparoscopic right colectomy. A total of 115 consecutive patients operated for right colon disease were identified, from September 1st 2014 to May 31st 2017. Patient demographics included age, gender, ASA score, past abdominal surgery, anticoagulant and steroid therapy, Diabetes Mellitus and preoperative diagnosis. The analysed outcomes included length of stay, operative time, blood loss, extraction site, postoperative complications (ileus, anastomotic failure and surgical site infection), reoperation rate, readmission rate and 30-day mortality. Results: The extracorporeal group included 84 and the intracorporeal group 31 patients. The intracorporeal group had less surgical site infections (3,2% versus 27,4%, p<0,05). There were no statistically significant differences in operative time, blood loss, ileus, anastomotic failure or mortality. Conclusion: Our study reveals similar outcomes for both intra- and extracorporeal anastomosis following laparoscopic right colectomy. Therefore, intracorporeal anastomosis seems to be a feasible and safe technique in the hands of experienced laparoscopic colorectal surgeons.